Genotoxicity and antioxidant enzyme activity induced by hexavalent chromium in Cyprinus carpio after in vivo exposure. (27th March 2013) - Kumar, Pavan; Kumar, Ravindra; Nagpure, Naresh S.; Nautiyal, Prakash; Kushwaha, Basdeo; Dabas, Anurag
Abstract: Fish, being an important native of the aquatic ecosystem, are exposed to multipollution states and are therefore considered as model organisms for ecotoxicological studies of aquatic pollutants, including metal toxicity. We investigated oxidative stress (OS) in liver, kidney and gill tissues through antioxidant enzyme activities and genotoxicity induced in whole blood and gill tissues through comet assay and micronucleus (MN) test in Cyprinus carpio after 96-hour in vivo static exposure to potassium dichromate at three sublethal (SL) test concentrations, including SL-I [93.95 mg/L, i.e. one quarter of half-maximal lethal concentration (LC50 )], SL-II (187.9 mg/L, i.e. one half of LC50 ), and SL-III (281.85 mg/L, i.e. three quarters of LC50 ), along with a control. The 96-hour LC50 value for potassium dichromate was estimated to be 375.8 mg/L in a static system in the test species. Tissues samples were collected at 24, 48, 72 and 96 hours postexposure. Results indicated that the exposed fish experienced OS as characterized by significant ( p < 0.05) variation in antioxidant enzyme activities, as compared to the control. Activities of superoxide dismutase and glutathione peroxidase increased, whereas activity of catalase decreased with the progression of the experiment. The mean percent DNA damage in comet tail and MN induction in gills and whole blood showed a concentration-dependent increase up to 96-hour exposure. The findings of this study would be helpful in organ-specific risk assessment of Cr(VI)-induced OS and genotoxicity in fishes.